Defect profiling of hot roll formed carbon-epoxy composite laminates during production - Land, Patrick (2018)
There is an increasing demand to utilise composite materials in the development of structural aerospace components such as wing spars and stringers. The high stiffness to weight ratio of these materials provide significant benefits to the fuel economy of the aircraft, particularly carbon composites. Current industrial research into the use of carbon-epoxy, uni-directional composite materials for structural applications has led to the requirement for greater innovation in the forming operations available to aerospace to increase practical application of their use. This has led to a need for new forming methods to enable more complex geometries such as double curvatures i.e. Z and U shape components and 3D surface geometries. The current critical limiting factor for aerospace when forming these next generation components is the occurrence of defects as a direct result of the forming process, as such the main requirement of this research is to provide a method of forming defect free thick carbon-epoxy stacks. The project partner, Airbus UK, is primarily interested in the formation of thick (>6 mm) thermoset carbon composite laminates. The Key findings of this research are as follows. The development of a novel forming technique, enabling the forming of pre-laid composite stacks in a single operation. During forming this process is then further analysed to correlate the effect of changes in process parameters to the formation of defects within the resulting material. These correlations are then used to optimize the forming process through control of elements during production. The approach taken in this research treats the material as an isotropic body, in that the make-up and structure of the composite is considered to be constant as changing these factors are outside the scope of the research. This places the focus of the research on evaluation of the relationship between material defects and changes in the factors/parameters that can be directly controlled and manipulated during forming. This research has developed a secondary forming method, hot roll forming, which has enabled the forming of thick thermoset composite laminates, over an aerospace representative mould tool. The research has used in-situ process monitoring and surface measurement techniques to analyse, characterise and optimise the forming process. Further understanding of the key defect forming parameter, applied load, has enabled the development and implementation of a closed loop control strategy to moderate and improve the application of this critical parameter, significantly reducing defect formation during hot roll forming. The developments and contributions gained from this research enable a more integrated use of composite materials within large structural aerospace components. This enhances process understanding and aids in removing barriers to the implementation of hot roll forming into wider industrial applications.